The in vitro pharmacological activities of Pericampylus glaucus (Lam.) Merr. and their relation to ethnomedicinal use - Shipton, F N (2017)
Malaysia’s rainforests have a great biodiversity, a lot of which has yet to be studied. This presents researchers with the opportunity for the discovery of new chemical structures which may be new leads in drug discovery. With problems such as antibiotic resistance and the need for improved drugs for the treatment of diseases such as cancer and neurodegenerative diseases, there is need for more research into drug discovery. The focus of the research covered in this document is on Pericampylus glaucus, a common climbing plant for which there is limited literature available. The aim of this study is to determine its pharmacological activities, based on what is known of its traditional use, in the hope that it can be used in the development of pharmaceutical drugs in the future.